Phytochemical Screening of Methanol Extract of Neem (Azadirachta indica) Leaves - Bahri, Syamsul; Hijriani, Baiq Isti; Widullutfi, Widullutfi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Neem (Azadirachta indica) is a highly respected medicinal plant and has been used in traditional medicine for centuries. The use of plants as medicine is important to know the secondary metabolite content in the plant. Phytochemical screening is a qualitative method aimed at tracing the presence of secondary metabolites contained in plants so that their potential as medicinal plants can be used. This research is an experimental laboratory using the maceration extraction method to obtain neem leaf extract. This research aims to identify secondary metabolite compounds contained in the ethanol extract of neem leaves. This study conducted flavonoid, tannin, alkaloid, steroid and saponin tests for the ethanol extract of neem leaves. The results obtained from the neem extract contain flavonoid, tannin, alkaloid, steroid and saponin compounds. In conclusion, phytochemical screening shows that the methanol extract of neem leaves (Azadirachta indica Juss) positively contains alkaloids, flavonoids, tannins, phenols, terpenoids, and steroids.